New records of Sturnira koopmanhilli (McCarthy, Albuja & Alberico, 2006) (Chiroptera, Phyllostomidae) from western and eastern Ecuador - Marco A. Rodríguez-Segovia; Laura Simba; Jorge Brito (Check List)
Sturnira koopmanhilli (McCarthy, Albuja & Alberico, 2006) is a rare and vulnerable bat species dis‑ tributed mainly in the Chocó biogeographic region of Ecuador and Colombia. A field expedition in north‑western Ecuador collected two new voucher specimens and tissues. We sequenced the whole cyt-b gene to confirm the taxonomic identity of these specimens. Furthermore, we reviewed three natural history collections to find unreported specimens. The present study provides seven new records for S. koopmanhilli in Ecuador and expands this species’ occurrence to the eastern slopes of the Andes.